Investigations on Regulation of MicroRNAs in Rice Reveal [Ca2+]cyt Signal Transduction Regulated MicroRNAs - Kansal, Shivani; Panwar, Vaishali; Mutum, Roseeta Devi; Raghuvanshi, Saurabh (Frontiers in Plant Science, 2021)
MicroRNAs are critical components of the multi-dimensional regulatory networks in eukaryotic systems. They regulate a spectrum of developmental and metabolic processes in both plants and animals. Thus, it is quite apparent that the transcription, processing as well as activity of the miRNAs themselves is very dynamically regulated. One of the most important and universally implicated signaling molecule is [Ca2+]cyt. It is known to regulate a plethora of developmental and metabolic processes in both plants and animals, however their impact on the regulation of miRNA expression is relatively less explored. The current study employed a combination of internal and external calcium channel inhibitors, to establish that [Ca2+]cyt signatures actively regulate miRNA expression in rice. Involvement of [Ca2+]cyt in regulation of miRNA expression was further confirmed by treatment with calcimycin, the calcium ionophore. Modulation of the cytosolic calcium levels was also found to regulate the drought responsive expression as well as ABA mediated response of miRNA genes in rice seedlings. The study further establishes the role of calmodulins and Calmodulin-binding Transcription Activators (CAMTAs) as important components of the signal transduction schema that regulates miRNA expression. Yeast-one-hybrid assay established that OsCAMTA4 & 6 are involved in the transcriptional regulation of miR156a and miR167h. Thus, the study was able to clearly establish that [Ca2+]cyt is actively involved in regulating expression of miRNA genes both under control and stress conditions.